Correction to: A Scan Strategy Based Compensation of Cumulative Heating Effects in Electron Beam Powder Bed Fusion (Progress in Additive Manufacturing, (2024), 10.1007/s40964-024-00807-6) - Breuning, Christoph; Markl, Matthias; Körner, Carolin (Progress in Additive Manufacturing, 2024)
The publication of this article unfortunately contained mistakes. Figure 7 was not correct. The corrected figure is given below. Wrong figure: (Figure presented.) Correct figure: (Figure presented.) The original article has been corrected.
CRIS-Team Scopus Importer:2025-02-04